A peptide mimic blocks the cross-reaction of anti-DNA antibodies with glomerular antigens. (8th December 2015) - Xia, Y; Eryilmaz, E; Der, E; Pawar, R D; Guo, X; Cowburn, D; Putterman, C
Summary: Anti-DNA antibodies play a pivotal role in the pathogenesis of lupus nephritis by cross-reacting with renal antigens. Previously, we demonstrated that the binding affinity of anti-DNA antibodies to self-antigens is isotype-dependent. Furthermore, significant variability in renal pathogenicity was seen among a panel of anti-DNA isotypes [derived from a single murine immunoglobulin (Ig)G3 monoclonal antibody, PL9-11] that share identical variable regions. In this study, we sought to select peptide mimics that effectively inhibit the binding of all murine and human anti-DNA IgG isotypes to glomerular antigens. The PL9-11 panel of IgG anti-DNA antibodies (IgG1, IgG2a, IgG2b and IgG3) was used for screening a 12-mer phage display library. Binding affinity was determined by surface plasmon resonance. Enzyme-linked immunosorbent assay (ELISA), flow cytometry and glomerular binding assays were used for the assessment of peptide inhibition of antibody binding to nuclear and kidney antigens. We identified a 12 amino acid peptide (ALWPPNLHAWVP, or 'ALW') which binds to all PL9-11 IgG isotypes. Preincubation with the ALW peptide reduced the binding of the PL9-11 anti-DNA antibodies to DNA, laminin, mesangial cells and isolated glomeruli significantly. Furthermore, we confirmed the specificity of the amino acid sequence in the binding of ALW to anti-DNA antibodies by alanine scanning. Finally, ALW inhibited the binding of murine and human lupus sera to dsDNA and glomeruli significantly. In conclusion, by inhibiting the binding of polyclonal anti-DNA antibodies to autoantigens in vivo, the ALW peptide (or its derivatives) may potentially be a useful approach to block anti-DNA antibody binding to renal tissue.